Erratum: Assessing sleepiness and sleep disorders in Australian long-distance commercial vehicle drivers: Self-report versus an "at home" monitoring device (Sleep (2012) 35:4 (469-75)) - Sharwood, L.; Elkington, J.; Stevenson, M.; Grunstein, R.; Meuleners, Lynn; Ivers, R.; Haworth, N.; Norton, R.; Wong, K. (Associated Professional Sleep Societies, Llc, 2013)
After some additional analysis of their data, the authors of the above paper discovered that the numbers in the published manuscript for “Substances to assist wakefulness” in Table 1, page 471, are slightly incorrect. All other data presented are correct. The corrected values are: Substances to assist wakefulness n-% Caffeinated beverages 251-48.5% Mod-high consumption*** 222-42.9% Energy Drinks 102-19.8% Mod-high consumption*** 86-16.6%